2018
DOI: 10.1164/rccm.201711-2348oc
|View full text |Cite
|
Sign up to set email alerts
|

Infant Viral Respiratory Infection Nasal Immune-Response Patterns and Their Association with Subsequent Childhood Recurrent Wheeze

Abstract: Distinct immune-response clusters during infant RSV infection and their association with risk of recurrent wheeze provide insights into the risk factors for and mechanisms of asthma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 73 publications
4
54
0
3
Order By: Relevance
“…However, it has been shown that lower blood TNF‐α levels in infants with RSV bronchiolitis were associated with greater disease severity and a longer hospital stay . Our finding is consistent with the study by Turi et al evaluating nasal immune response phenotypes in infants with RSV infection in which they demonstrated low non‐IFN antiviral immune response, including TNF‐α, as significantly associated with recurrent wheezing in the first and second‐year following RSV infection. In the upper airways, a decrease in IL‐10 potentiates an increase in the TNF‐α response which controls the viral infection .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, it has been shown that lower blood TNF‐α levels in infants with RSV bronchiolitis were associated with greater disease severity and a longer hospital stay . Our finding is consistent with the study by Turi et al evaluating nasal immune response phenotypes in infants with RSV infection in which they demonstrated low non‐IFN antiviral immune response, including TNF‐α, as significantly associated with recurrent wheezing in the first and second‐year following RSV infection. In the upper airways, a decrease in IL‐10 potentiates an increase in the TNF‐α response which controls the viral infection .…”
Section: Discussionsupporting
confidence: 92%
“…Although it is known that infants with severe RSV bronchiolitis have increased risks of recurrent wheezing and asthma in later life, previous literature on roles of innate and adaptive cytokines in the pathogenesis of subsequent wheeze following acute severe RSV bronchiolitis have been limited. 9 In our study, we have demonstrated impaired T A B L E 2 Peripheral blood CD4+CD25 hi Foxp3 hi cells and granzyme B expression and cytokine production from CD3/CD46-activated and CD3/CD28-activated CD4+ cells during severe RSV bronchiolitis in infancy by wheezing outcome Note: Data were subtracted from negative control conditions (PBS) and negative data were adjusted to zero, then log-transformed for statistical analysis. Abbreviations: IFN-γ, interferon-γ; IL, Interleukin; TNF-α, tumor necrosis factor-α.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations